WAYANG GOLEK RINGAN PEMANFAATAN LIMBAH SEBAGAI PENGEMBANGAN BONEKA WAYANG GOLEK - Trisno Santoso (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Wayang Golek Ringan (Light Marionette Puppet) Waste Utilisation in Developing Wayang golek is a new modification model in making Wayang golek in order to avoid logging. The novelties in the creation of this wayang puppet are presented in its elements, namely the core material, fashion, make-up, and the connection of the limbs of the puppet. The material used in making the puppet are sawdust (Javanese:grajèn), or recycles paper pulp (papier mâché), cement paper bags, dacron, patchworks. And used styrofoam. The research used a combination method of field work including observation, interview, literature study, Particioan Art Research Technique (PART), FGD, exploration, and empirical method. The combination of the methods was used to collect, classify and analyse the data as well as in the process of creating the puppet. The main purpose of the change of the core material in making the puppet is to preserve the environment by decreasing the logging which may result in the environmental damage.